The Influence of Brand Trust and Price Perception on Purchase Decisions at Rotte Bakery Pasir Putih Branch - Asep Duduh Abdurahman; Muhammad Hidayat; Nefrida; Irsyadi Zain; Mulyani Rody Muin (Jurnal Ekonomi dan Bisnis Digital, 2023)
This research aims to determine the influence of brand trust and price perception on purchasing decisions at the Rotte Bakery Pasir Putih branch. This research is quantitative research with brand trust and price perception variables on purchasing decisions. This research uses data collection techniques by distributing questionnaires. The total sample for this research was 97 respondents taken using the lameshow technique. The data analysis techniques used are descriptive statistical analysis techniques and inferential statistics. The research results show that brand trust partially influences purchasing decisions and price perception partially influences purchasing decisions. Meanwhile, brand trust and price perception have a simultaneous influence on purchasing decisions. Then it was also discovered that the contribution to the presentation of influence provided by brand trust and price perception was 73.8% and the remaining 26.2% came from other variables not included in this research. It can be concluded that brand trust and price perception influence purchasing decisions at Rotte Bakery Pasir Putih Branch.